Structuring of the soil microbiome by the use of silicate rock powders - Oliveira, Rafael Lima (2024)
The increasing global population and food demand underscore the necessity for the development of sustainable agricultural systems that incorporate advanced technologies and the reuse of waste materials. Optimizing the use of locally available fertilizers and soil conditioners is crucial for enhancing tropical soil management, reducing reliance on imported fertilizers, and maintaining or improving agricultural productivity to ensure food security. Despite its importance, the interactions between rock powders and tropical soils-considering their varied chemical, physical, and biological characteristics-are not well understood. Here, we evaluated the effects of different rock powders on tropical soil properties and their interactions with microbial communities. We applied diabase, phonolite, or granite at rates of 0.00, 1.50, 3.00, and 5.00 Mg ha-1 to pots containing Typic Dystrophic Red Yellow Ferrosol and Eutrophic Red Nitosol and assessed the morphological and nutritional responses of Urochloa brizantha cv. Marandu over 300 days. Our findings indicate that rock powder applications significantly impacted soil chemistry and biology, particularly potassium availability and plant biomass production, with the most pronounced benefits observed at a dose of 1.5 Mg ha-1. Granite treatments were particularly effective, resulting in increased dry matter production and potassium accumulation. We observed significant changes in soil chemistry, especially in exchangeable potassium content, with granite exhibiting the highest potassium levels. Enzymatic activity varied by soil type, reflecting both natural soil fertility and the chemical changes induced by rock powder applications. Molecular analyses of fungal diversity showed that rock powders influenced alpha diversity, with increased richness and diversity in treatments with granite and diabase. Changes in microbial community structure, particularly in the ITS region, were correlated with nutritional parameters such as potassium accumulation in plant dry matter. Co-occurrence network analyses revealed a dominance of five major phyla and increased positive interactions with rock powder amendments, indicating that bacterial genera involved in mineral weathering had the highest connectivity. These results elucidate the complex dynamics of rock powder use, highlighting its effects on plant responses, soil chemistry, and microbial community interactions in tropical soils.